PENERAPAN METODE SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) UNTUK MENGHILANGKAN KEBIASAAN MEROKOK KALANGAN REMAJA - Nurnaningsih Nurnaningsih (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
The problem of smoking is a problem that is being faced by various countries, the level is not only national but has become an international problem. Many trigger factors that cause everyone to do smoking behavior, even like a vicious circle because one with the other interconnected. In terms of various aspects, all agreed that smoking is detrimental to health, even the packaging clearly stated that smoking can cause cancer and blood vessel blockage which will lead to death. Because the effects caused by smoking are very dangerous for the perpetrators and the environment, let alone have an impact on children and adolescents so that they realize it or not have set a bad example for the next generation The phenomenon of smoking among adolescents at this time is increasing in number, therefore we need a method of therapy to reduce or even eliminate teenage addictions in smoking. Spiritual Emotional Freedom Technique (SEFT) is believed to eliminate smoking addiction. Preliminary study results from Pre-cycle show that the level of smoking habits of adolescents is high, namely 75% of students in the heavy category (addicted to smoking) and as much as 25% in the moderate category. By using the Therapy SEFT, the level of smoking addiction decreased significantly, which is included in the weight category after treatment decreased to 60%, and the moderate category after treatment decreased to 10%. Thus the level of smoking habits of adolescents who are addicted to smoking both in the category of heavy and moderate, effective enough to reduce or even eliminate the smoking habits of teenagers.